NF-κB regulates brown adipocyte function through suppression of ANT2 - Shiqiao Peng; Xiaoying Zhang; Lili Yu; Yanhong Xu; Yang Zhou; Shengnan Qian; Xinyu Cao; Xiaotong Ye; Jiajun Yang; Weiping Jia; Jianping Ye (Elsevier, 2022)
The transcription factor nuclear factor of kappa-light-chain-enhancer of activated B cells (NF-κB) is expressed in brown adipocytes, but its role remains largely unknown in the cells. This issue was addressed in current study by examining NF-κB in brown adipocytes in vitro and in vivo. NF-κB activity was increased by differentiation of brown adipocytes through elevation of p65 (RelA) expression. The transcriptional activity of NF-κB was induced by the cold stimulation with an elevation in S276 phosphorylation of p65 protein. Inactivation of NF-κB in brown adipocytes made the knockout mice [uncoupling protein 1 (Ucp1)-CreER-p65f/f, U-p65-KO] intolerant to the cold environment. The brown adipocytes exhibited an increase in apoptosis, a decrease in cristae density and uncoupling activity in the interscapular brown adipose tissue (iBAT) of p65-KO mice. The alterations became severer after cold exposure of the KO mice. The brown adipocytes of mice with NF-κB activation (p65 overexpression, p65-OE) exhibited a set of opposite alterations with a reduction in apoptosis, an increase in cristae density and uncoupling activity. In mechanism, NF-κB inhibited expression of the adenine nucleotide translocase 2 (ANT2) in the control of apoptosis. Data suggest that NF-κB activity is increased in brown adipocytes by differentiation and cold stimulation to protect the cells from apoptosis through down-regulation of ANT2 expression.